Classification of living organisms - Lewis, Mark J. 4 0 16; 5 (New York : Rosen Publishing, 2011)
An exploration of genetics that focuses on the classification of living organisms and discusses changes in the science of classification.
Early classification -- A modern system is born -- Evolutionary relationships : the dawn of phylogenetics -- Cladistics -- The ever-changing science of classification.
Includes bibliographical references (p. 73-76) and index.
7.7;Young Adult;Young Adult.
Keywords: 2 -- 0; 6; Biology -- 20 -- Classification;Juvenile literature; 20; 2